Deciphering the Function of Octopaminergic Signaling on Wing Polyphenism of the Pea Aphid Acyrthosiphon pisum - Wang, Xing-Xing; Zhang, Yi; Zhang, Zhan-Feng; Tian, Hong-Gang; Liu, Tong-Xian (Frontiers in Physiology, 2016)
Aphids exhibit wing polyphenism (winged or wingless) for adaption to predictable or temporally heterogeneous environmental changes; however, the underlying mechanism is still unclear. This morphological change could be stimulated by high aphid density, which in turn could affect octopaminergic signaling in aphids. Octopamine is a neurotransmitter synthesized in insects that can modify their physiological metabolism, locomotion, and other behaviors. We designed experiments to determine whether octopamine functions in wing formation of the pea aphid, Acyrthosiphon pisum (Harris). We determined gene expression of tyramine β-hydroxylase (TβH), a key enzyme in octopamine synthesis at different developmental stages, in different body parts, and in different densities of aphids. We also used TβH RNAi, octopamine receptor agonists (octopamine and synephrine), and an antagonist (mianserin) to modify octopaminergic signaling. We found that transcription of TβH was related to aphid density, which affected the proportion of winged offspring. By manually modifying the mother’s octopaminergic signaling, TβH expression was suppressed, and TβH (enzyme) activity decreased. The proportion of winged offspring was also affected. Our results showed that octopamine could be a link in the wing determination system, as well as environmental stimulation. The RNAi results showed that the decrease of TβH expression increased aphid’s reproduction; however, the decrease of TβH expression declined the numbers of winged-offspring producers, but did not affect the proportion of winged nymphs produced by the winged-offspring producer. In conclusion, the decline in the proportion of winged daughters in the next generation was caused by the decline of winged nymph producers.